Gut microbiota is associated with adiposity markers and probiotics may impact specific genera - Gomes, Aline Corado; Hoffmann, Christian; Mota, João Felipe (European journal of nutrition, 2020)
Purpose It has been suggested that restoring gut microbiota alterations with probiotics represents a potential clinical target for the treatment of gut microbiota-related diseases, such as obesity. Here, we apply 16S rDNA microbiota profiling to establish which bacteria in the human gut are associated with obesity and cardiometabolic risk factors, and to evaluate whether probiotic supplementation modulates gut microbiota. Methods We evaluated the effects of a probiotic mixture (2 × 10 10 CFU/day of Lactobacillus acidophilus LA-14, Lactobacillus casei LC-11, Lactococcus lactis LL-23, Bifidobacterium bifidum BB-06, and Bifidobacterium lactis BL-4) in 32 overweight or obese women in a double-blind, randomized, placebo-controlled study. Using 16S rDNA sequencing, we characterized fecal samples and investigated the relationships between microbiome data and diet, body composition, antioxidant enzymes, and inflammatory profile. In addition, we characterized the degree of variation among fecal communities after the intervention. Results BMI, weight, fat mass, lean mass, conicity index, protein intake, monounsaturated fat intake, glycated hemoglobin, TNF-α, and IL6/IL10 were significantly correlated with microbiome composition. The candidate division TM7 was strongly associated with all adiposity markers and Clostridiaceae associated negatively with TNF-α. The family Clostridiaceae increased and TM7 tended to decrease after the probiotic mixture supplementation. Subjects were clustered according to body composition, and a higher proportion of TM7 was observed in those with higher adiposity. Conclusions Ecosystem-wide analysis of probiotic use effects on the gut microbiota revealed a genera specific influence, and one of which (TM7) represents a promising novel target for obesity treatment. Trial registration number U1111-1137-4566.